Model doskonałości EFQM dla małych i średnich firm w gospodarstwach rolnych - Mongiało, Zbigniew (EFQM Excellence Model for SMEs in Farms, 2005)
The paper presents a general model scheme of quality awards for farms. The scheme is developed on the basis of the EFQM excellence model for SMEs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 108-112